Answer:
-5 - 3x > 10
Step-by-step explanation:
x = -6
Plug in the x value for each inequality:
-5 - 3(-6) > 10
-5 + 18 > 10
13 > 10
True
-3 - 5(-6) < -14
-3 + 30 < -14
27 < -14
False
1 - 2(-6) > 13
1 + 12 > 13
13 > 13
False
2 - (-6) < -3
2 + 6 < -3
8 < -3
False
Only one of these is true; that is the answer.
Answer:
I hope this helps!
Step-by-step explanation:
3y(5x+3)=15yx+9y
2y(2x+3)=4yx+6y
4y(x+2)=4yx+8y
3y(7x+2)=21yx+6y
So g(x) doesn't come in
ok
remember pemdas
inside first
evaluate f(4)
f(4)=4^2+1=16+1=17
now we have
[17]^2=289
answer s 289
The answer b your welcome so much
Answer:
5p+s
Step-by-step explanation:
five friends jumping for one hour